2020
DOI: 10.2169/internalmedicine.4937-20
|View full text |Cite
|
Sign up to set email alerts
|

Mucinous Cystadenocarcinoma of the Pancreas with Cyst Infection in a Male Patient

Abstract: Follow-up computed tomography revealed a 40-mm pancreatic tail cyst in a 59-year-old man with type 1 diabetes mellitus. An intraductal papillary mucinous neoplasm was suspected; mucinous cystic neoplasm (MCN) was not considered because the patient was a man. During follow-up, cyst infection occurred but was improved by conservative treatment. At the 24-month follow up examination, cyst nodules had developed, corresponding to an increase in the carbohydrate antigen 19-9 level. Mucinous cystadenocarcinoma (MCC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
(26 reference statements)
1
1
0
Order By: Relevance
“…We also thank Ms. Shuko Nojiri, Associate Professor at the Medical Technology Innovative Center and Clinical Research and Trial Center, Juntendo University, for statistical advice. One case of MCN (the case in a male patient) in this study cohort was reported as a case report by Tomishima et al 20 .…”
Section: Acknowledgementssupporting
confidence: 54%
“…We also thank Ms. Shuko Nojiri, Associate Professor at the Medical Technology Innovative Center and Clinical Research and Trial Center, Juntendo University, for statistical advice. One case of MCN (the case in a male patient) in this study cohort was reported as a case report by Tomishima et al 20 .…”
Section: Acknowledgementssupporting
confidence: 54%
“…We also thank Ms. Shuko Nojiri, Associate Professor, Medical Technology Innovative Center, Clinical Research and Trial Center, Juntendo University, for statistical advice. One case of MCN (male case) in this study cohort was reported as a case report by Tomishima et al 19 Author contributions Y.F., Y.K., Y.M., M.Tak. and M.To.…”
Section: Acknowledgementsmentioning
confidence: 80%